Exploration of hydrocarbon degrading bacteria on soils contaminated by crude oil from South Sumatera - A Napoleon; D S Probowati (Journal of Degraded and Mining Lands Management, 2014)
The goal of this research was to explore hydrocarbon degrading bacteria on crude oil contaminated soil with potential to degrade hydrocarbon in oil pollutant. The research started by early August 2013 till January 2014. Soil sampling for this research was taken on several places with contaminated soil location such as Benakat, Rimau, and Pengabuan all of it located in South Sumatera. Conclusion from this research Isolates obtained from three (3) sites of contaminated soil and treated using SBS medium were Bacillus cereus, Pseudomonas aeruginosa, Klebsiella pnumoniae, Streptococcus beta hemolisa, Proteus mirabilis, Staphylococcus epidermis and Acinotobacter calcoaceticus. Isolates that survived on 300 ppm of hydrocarbon concentration were Bacillus cereus, Pseudomonas aeruginosa and Acinetobacter cakciaceticus Selected isolates posses the ability to degrade hydrocarbon by breaking hydrocarbon substance as the energy source to support isolates existence up to 1,67 TPH level. Based on results accomplish by this research, we urge for further research involving the capacity of isolates to degrade wide variety of hydrocarbon substance and more to develop the potential of these bacteria for bioremediation.